Jane Eyre - Zeffirelli, Franco; Hurt, William; Gainsbourg, Charlotte, 1971-; Plowright, Joan.; Paquin, Anna.; Bronte, Charlotte, 1816-1855.; Miramax Films; Rochester Films, Ltd.; Miramax Home Entertainment (Firm); Buena Vista Home Entertainment (Firm) (Burbank, Calif. : Miramax Home Entertainment : Distributed by Buena Vista Home Video, 2003)
The harshly treated orphan girl, Jane Eyre, becomes a governess in an mysterious Yorkshire mansion and falls in love with the master of the house.
Based on the novel by Charlotte Bronte, Anna Paquin.
For specific features see interactive menu.
"28669"--Container.
Director of photography, David Watkin ; editor, Richard Marden ; music, Alessio Vlad, Claudio Capponi.
William Hurt, Charlotte Gainsbourg, Joan Plowright.
MPAA rating: PG-13.
Keywords: Man-woman relationships -- England -- Drama; Young women -- England -- Drama; Governesses -- England -- Drama; Video recordings for hard of hearing people; England -- Social life and customs -- 19th century -- Drama; Feature films